2017
DOI: 10.1111/1751-7915.12747
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐fermentation triggering population selection in mixed‐culture glycerol fermentation

Abstract: SummaryElectro‐fermentation is a new technique that could be used to influence the global metabolism in mixed‐culture fermentation. In this study, a mixed‐culture cathodic electro‐fermentation of glycerol was investigated. Both microbial community structure and metabolic patterns were altered when compared to standard fermentation. This microbial population shift was more significant when the working electrodes were pre‐colonized by Geobacter sulfurreducens, before electro‐fermentation. The electro‐fermenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 28 publications
0
22
1
Order By: Relevance
“…This sudden increase in the pH caused a significant decrease in the production of methane by 43%. In contrast to the above study, in another research [89], it was observed that when using a two-chamber cell with a short HRT for about 3 days, with an applied voltage of 0.6 V, a significant increase was observed in methane production. Nevertheless, voltage conditions of 1.0 V and 2.0 V decreased the production of methane by 37%.…”
Section: Applied Voltage As a Power Sourcecontrasting
confidence: 76%
“…This sudden increase in the pH caused a significant decrease in the production of methane by 43%. In contrast to the above study, in another research [89], it was observed that when using a two-chamber cell with a short HRT for about 3 days, with an applied voltage of 0.6 V, a significant increase was observed in methane production. Nevertheless, voltage conditions of 1.0 V and 2.0 V decreased the production of methane by 37%.…”
Section: Applied Voltage As a Power Sourcecontrasting
confidence: 76%
“…Therefore, it is reasonable to think that the redox potential value inside bioreactors can affect the metabolite generation and, therefore, the spectrum of products obtained depending on the extracellular redox conditions. In fact, electrofermentation is a novel technique that is being used to change the overall performance in mixed-culture fermentations, by altering both microbial community structure and metabolic patterns [30]. Also, electrochemical control of the redox potential in mixed culture bioreactors has been shown to regulate microbial metabolites production [31].…”
Section: Resultsmentioning
confidence: 99%
“…Here, with their recent work published in the issue, Moscoviz et al. () proved that the electro‐fermenting microbial community was more efficient for producing 1,3‐propanediol when compared with fermentation controls…”
mentioning
confidence: 81%